Use of Laser Assisted Optical Rotational Cell Analyzer (LoRRca MaxSis) in the Diagnosis of RBC Membrane Disorders, Enzyme Defects, and Congenital Dyserythropoietic Anemias: A Monocentric Study on 202 Patients - Zaninoni, Anna; Fermo, Elisa; Vercellati, Cristina; Consonni, Dario; Marcello, Anna P.; Zanella, Alberto; Cortelezzi, Agostino; Barcellini, Wilma; Bianchi, Paola (Frontiers in Physiology, 2018)
Chronic hemolytic anemias are a group of heterogeneous diseases mainly due to abnormalities of red cell (RBC) membrane and metabolism. The more common RBC membrane disorders, classified on the basis of blood smear morphology, are hereditary spherocytosis, elliptocytosis, and hereditary stomatocytoses. Among RBC enzymopathies, the most frequent is pyruvate kinase deficiency, followed by glucose-6-phosphate isomerase, pyrimidin 5’ nucleotidase, and other rare enzymes defects. Because of the rarity and heterogeneity of these diseases, diagnosis may be often challenging despite the availability of a variety of laboratory tests. The ektacytometer laser-assisted optical rotational cell analyser (LoRRca MaxSis), able to assess the RBC deformability in osmotic gradient conditions (Osmoscan analysis), is a useful diagnostic tool for RBC membrane disorders and in particular for the identification of hereditary stomatocytosis. Few data are so far available in other hemolytic anemias. We evaluated the diagnostic power of LoRRca MaxSis in a large series of 140 patients affected by RBC membrane disorders, 37 by enzymopathies and 16 by congenital diserythropoietic anemia type II. Moreover, 9 patients with paroxysmal nocturnal hemoglobinuria were also investigated. All the hereditary spherocytoses, regardless the biochemical defect, showed altered Osmoscan curves, with a decreased Elongation Index max and right shifted Omin; hereditary elliptocytosis displayed a trapezoidal curve and decreased EImax. Dehydrated hereditary stomatocytosis caused by PIEZO1 mutations was characterized by left-shifted curve, whereas KCNN4 mutations were associated with a normal curve. Congenital diserythropoietic anemia type II and RBC enzymopathies had Osmoscan curve within the normal range except for glucosephosphate isomerase deficient cases who displayed an enlarged curve associated with significantly increased Ohyper, offering a new diagnostic tool for this rare enzyme defect. The Osmoscan analysis performed by LoRRca MaxSis represents a useful and feasible first step screening test for specialized centers involved in the diagnosis of hemolytic anemias. However, the results should be interpreted by caution because different factors (i.e. splenectomy or coexistent diseases) may interfere with the analysis; additional tests or molecular investigations are therefore needed to confirm the diagnosis.